Business survival in portuguese regions - Nunes, Alcina (2011)
This work addresses the post-entry performance of employer enterprises for seven regions in Portugal, at the NUT II level, by investigating the structural characteristics of survival, using non-parametric and semi-parametric methods, during the period 1985 to 2007. The last decades of the 20th century were characterized by a period of creative destruction in Portugal. In particular, regions such as Norte, Algarve and Madeira show the highest growth rates in enterprise births, deaths and firm churn. After 2000, firms´ births and deaths get relatively less turbulent. In the non-parametric analysis, we identify statistically significant disparities among regions. Norte has the lowest survival rate and Centro holds the longest surviving firms and the survival gap between the former two regions gets amplified over time. Concerning the semiparametric analysis, firm’s current size dimension is a strong determinant for the probability of survival, particularly in the Norte and Açores. In industries characterized by high entry rates at the moment of a firm’s birth, post-entry survival becomes harder, especially in the south and in the Portuguese archipelagos, the regions with the lowest number of active employer enterprises. A higher entry rate combined with fast growth rates for any given industry also generates a shorter duration of firms. Manufacturing is the sector where more firms are more likely to abandon the market, particularly in Madeira and Norte. But it is turbulence, given by the sum of firms´ entry and exit rates that exhibits the most significant effect on survival. For every region, except for the Açores, where there is no statistical significance, those that have the highest record of firm turbulence, also display the lowest business survival probabilities. Turbulence decreases severely the survival probabilities of firms located in Madeira and Norte and to a lesser extent in the Algarve.